Hubungan antara Literasi Kesehatan Mental dengan Kecenderungan Diagnosis Diri pada Mahasiswa Fakultas Kesehatan Masyarakat Universitas Nusa Cendana Kupang - Yohanes Jonathan Anggul; Feronika Ratu; Mernon Yerlinda C. Mage (Jurnal Ilmu Kesehatan dan Gizi, 2026)
Students in the transition period are vulnerable to experiencing mental health problems and tend to self-diagnose due to easy access to information and low mental health literacy. This research aims to determine the relationship between mental health literacy and the tendency to make a diagnosis in students at the Faculty of Public Health, Nusa Cendana University, Kupang. This type of research is quantitative research with a correlational approach. Respondents in this study totaled 298 using purposive sampling techniques. Data collection techniques used the mental health literacy scale and self-diagnosis scale. Data analysis used the Spearman Rank test. The results showed that there was a significant negative relationship between mental health literacy and self-diagnosis (r = -0.156; p = 0.007, p < 0.05). Although significant, the strength of this relationship is in the weak category, indicating that the tendency to self-diagnosis is not only determined by the level of mental health literacy. Other factors such as the intensity of exposure to mental health content on social media, the tendency of students to only seek information that supports the results of their self-diagnosis, as well as the influence of academic pressure and the normalization of mental disorders among peers are thought to contribute to this behavioral tendency. It is hoped that students not only have a high level of mental health literacy but also quality, so that they realize that self-diagnosis is an inappropriate action and students are expected to take advantage of available professional mental health services.